Answer:
![2*log(x)+log(y)](https://tex.z-dn.net/?f=2%2Alog%28x%29%2Blog%28y%29)
Step-by-step explanation:
So, there are two logarithmic identities you're going to need to know.
<em>Logarithm of a power</em>:
![log_ba^c=c*log_ba](https://tex.z-dn.net/?f=log_ba%5Ec%3Dc%2Alog_ba)
So to provide a quick proof and intuition as to why this works, let's consider the following logarithm: ![log_ba=x\implies b^x=a](https://tex.z-dn.net/?f=log_ba%3Dx%5Cimplies%20b%5Ex%3Da)
Now if we raise both sides to the power of c, we get the following equation: ![(b^x)^c=a^c](https://tex.z-dn.net/?f=%28b%5Ex%29%5Ec%3Da%5Ec)
Using the exponential identity: ![(x^a)^c=x^{a*c}](https://tex.z-dn.net/?f=%28x%5Ea%29%5Ec%3Dx%5E%7Ba%2Ac%7D)
We get the equation: ![b^{xc}=a^c](https://tex.z-dn.net/?f=b%5E%7Bxc%7D%3Da%5Ec)
If we convert this back into logarithmic form we get: ![log_ba^c=x*c](https://tex.z-dn.net/?f=log_ba%5Ec%3Dx%2Ac)
Since x was the basic logarithm we started with, we substitute it back in, to get the equation: ![log_ba^c=c*log_ba](https://tex.z-dn.net/?f=log_ba%5Ec%3Dc%2Alog_ba)
Now the second logarithmic property you need to know is
<em>The Logarithm of a Product</em>:
![log_b{ac}=log_ba+log_bc](https://tex.z-dn.net/?f=log_b%7Bac%7D%3Dlog_ba%2Blog_bc)
Now for a quick proof, let's just say: ![x=log_ba\text{ and }y=log_bc](https://tex.z-dn.net/?f=x%3Dlog_ba%5Ctext%7B%20and%20%7Dy%3Dlog_bc)
Now rewriting them both in exponential form, we get the equations:
![b^x=a\\b^y=c](https://tex.z-dn.net/?f=b%5Ex%3Da%5C%5Cb%5Ey%3Dc)
We can multiply a * c, and since b^x = a, and b^y = c, we can substitute that in for a * c, to get the following equation:
![b^x*b^y=a*c](https://tex.z-dn.net/?f=b%5Ex%2Ab%5Ey%3Da%2Ac)
Using the exponential identity:
, we can rewrite the equation as:
![b^{x+y}=ac](https://tex.z-dn.net/?f=b%5E%7Bx%2By%7D%3Dac)
taking the logarithm of both sides, we get:
![log_bac=x+y](https://tex.z-dn.net/?f=log_bac%3Dx%2By)
Since x and y are just the logarithms we started with, we can substitute them back in to get: ![log_bac=log_ba+log_bc](https://tex.z-dn.net/?f=log_bac%3Dlog_ba%2Blog_bc)
Now let's use these identities to rewrite the equation you gave
![log(x^2y)](https://tex.z-dn.net/?f=log%28x%5E2y%29)
As you can see, this is a log of products, so we can separate it into two logarithms (with the same base)
![log(x^2)+log(y)](https://tex.z-dn.net/?f=log%28x%5E2%29%2Blog%28y%29)
Now using the logarithm of a power to rewrite the log(x^2) we get:
![2*log(x)+log(y)](https://tex.z-dn.net/?f=2%2Alog%28x%29%2Blog%28y%29)